Differential Effects of Axon Initial Segment and Somatodendritic Gaba a Receptors on Excitability Measures in Rat Dentate Granule Neurons - Rojas-Montecinos, P (2011)
GABAA receptors are found on the somatodendritic compartment and on the axon initial segment of many principal neurons. The function of axonal receptors remains obscure, although it is widely assumed that axonal receptors must have a strong effect on excitability. We found that activation of GABA A receptors on the dentate granule neuron axon initial segment altered excitability by depolarizing the voltage threshold for action potential initiation under conditions that minimally affected overall cell input resistance. In contrast, activation of somatic GABAA receptors strongly depressed the input resistance of granule neurons without affecting the voltage threshold of action potential initiation. Although these effects were observed over a range of intracellular chloride concentrations, average voltage threshold was unaffected when ECl rendered GABAA axon initial segment responses explicitly excitatory. A compartment model of a granule neuron confirmed these experimental observations. Low ambient agonist concentrations designed to activate granule neuron tonic currents did not stimulate axonal receptors sufficiently to raise voltage threshold. Using excitatory postsynaptic current (EPSC)-like depolarizations, we show physiological consequences of axonal versus somatic GABAA receptor activation. With axonal inhibition, individual excitatory postsynaptic potentials (EPSPs) largely retained their amplitude and time course, but EPSPs that were suprathreshold under basal conditions failed to reach threshold with GABAA activation. By contrast, somatic inhibition depressed individual EPSPs because of strong shunting. Our results suggest that axonal GABAA receptors have a privileged effect on voltage threshold and that two major measures of neuronal excitability, voltage threshold and rheobase, are differentially affected by axonal and somatic GABAA receptor activation. Copyright © 2011 The American Physiological Society.